(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
The possibility of obtaining acrylamid-vinyl alcohol copolymer from alkaline saponification of acrylamid-vinyl acetate copolymer was confirmed by IR spectral method. The hydrodinamical behavior of the saponified copolymer was studied by viscosimetry. It was shown that the saponified copolymer has high viscosity and aberrant behavior characteristic for polyelectrolyts.